1995
DOI: 10.1128/jb.177.17.4963-4968.1995
|View full text |Cite
|
Sign up to set email alerts
|

Intragenic recombination of a single plant pathogen gene provides a mechanism for the evolution of new host specificities

Abstract: Gene pthA is required for virulence of Xanthomonas citri on citrus plants and has pleiotropic pathogenicity and avirulence functions when transferred to many different xanthomonads. DNA sequencing revealed that pthA belongs to a family of Xanthomonas avirulence/pathogenicity genes characterized by nearly identical 102-bp tandem repeats in the central region. By inserting an nptI-sac cartridge into the tandemly repeated region of pthA as a selective marker, intragenic recombination among homologous repeats was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 36 publications
(53 reference statements)
1
55
0
2
Order By: Relevance
“…Intragenic recombination amongst tandem repeats in a single gene in Xanthomonas campestris pv. maluacearum provide a mechanism for the evolution of new host specificities (Yang & Gabriel, 1995). Surface proteins displaying reiterated repeats are increasingly being reported in mycoplasmas (Proft et al, 1995;Zheng et al, 1995;Zhang & Wise 1996) and phylogenetically related Grampositive bacteria (Wren, 1991 ;Wastfelt et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Intragenic recombination amongst tandem repeats in a single gene in Xanthomonas campestris pv. maluacearum provide a mechanism for the evolution of new host specificities (Yang & Gabriel, 1995). Surface proteins displaying reiterated repeats are increasingly being reported in mycoplasmas (Proft et al, 1995;Zheng et al, 1995;Zhang & Wise 1996) and phylogenetically related Grampositive bacteria (Wren, 1991 ;Wastfelt et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…pthA contains 17.5 copies of a nearly identical tandem repeat unit that encodes 34 amino acids and is responsible for pathogenicity and host specificity (50). It undergoes intragenic recombination resulting in rapid adaptations to new hosts (9,52), while the expression of pthA within plant cells elicits division, enlargement, and cell death, mimicking canker (14). Genes that contain coding tandem repeats often encode proteins with diverse functions, and the variable numbers of tandem repeats affect the pathogenicity or antigenicity in several human/animal pathogens, such as Treponema denticola and Streptococcus agalactiae (23,35,36).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there are no reports of natural mechanisms of how new avr genes or race differentiation are generated. Mutational analyses of avrBs3/ pth genes revealed that the order and type of repeats in the central domain were important for race-specificity or pathogen fitness 3,38,39 . In general, repetitive regions of DNA are known to be active sites for homologous recombination 28 .…”
Section: Fig 5 Conservation Of Xoo Genes In Xac and Xccmentioning
confidence: 99%